reCode: A Lightweight Find-and-Replace Interaction in the IDE for Transforming Code by Example - Ni, Wode; Sunshine, Joshua; Le, Vu; Gulwani, Sumit; Barik, Titus (UIST 2021, 2021)
Software developers frequently confront a recurring challenge of making code transformations—similar but not entirely identical code changes in many places—in their integrated development environments. Through formative interviews (???? = 7), we found that developers were aware of many tools intended to help with code transformations, but often made their changes manually because these tools required too much expertise or effort to be able to use effectively. To address these needs, we built an extension for Visual Studio Code, called reCode. reCode improves the familiar find-and-replace experience by allowing the developer to specify a straightforward search term to identify relevant locations, and then demonstrate their intended changes by simply typing a change directly in the editor. Using programming by example, reCode automatically learns a more general code transformation and displays these transformations as before-and-after differences inline, with clickable actions to interactively accept, reject, or refine the proposed changes. In our usability evaluation (???? = 12), developers reported that this mixed-initiative, example-driven experience is intuitive, complements their existing workflow, and offers a unified approach to conveniently tackle a variety of common yet frustrating scenarios for code transformations.